The current status of Pogonodon Cope, 1880 (Carnivora: Nimravidae) and a substitution name for its junior homonym Pogonodon Bouchet, 1997 (Caenogastropoda: Triphoridae) - Vinola-Lopez, Lazaro W.; Bouchet, Philippe (Zootaxa, 2020)
This nomenclatural note addresses the problem regarding the taxonomic status of the extinct large nimravid Pogonodon Cope, 1880 (Chordata. Mammalia, Nimravidae), from the Oligocene of North America and its junior homonym, the recent triphorid marine snail Pogonodon Bouchet, 1997 (Mollusca, ) from the Mediterranean. Here we propose Ionthoglossa nov. gen. as a substitute name for the latter and provide a brief history of the two taxa from the literature available.